Hearing protection : selection factors and risks of excessive attenuation - Matos, Maria Luísa Ferreira (2014)
Currently, noise exposure in the occupational setting continues to be a problem in industrialized countries, not only because this is the most common occupational disease in these countries, but also because it is transversal to all activity sectors, including leisure activities. Exposure to high noise levels can affect the hearing system. For this reason, the legislation requires that the employer implements a set of measures to protect the exposed worker, and as last solution the use of individual hearing protection. However, what occurs in practice and in the majority of cases is the adoption of the use of hearing protection, at the expense of collective protective measures. Nevertheless, not always their selection is made of the most efficient manner. Excessive attenuation of the protectors, as well as the existence of sectors where impulsive noise is produced, are currently the main concerns of safety technicians.